2019
DOI: 10.1136/thoraxjnl-2018-212726
|View full text |Cite
|
Sign up to set email alerts
|

Heat-moulded versus custom-made mandibular advancement devices for obstructive sleep apnoea: a randomised non-inferiority trial

Abstract: RationaleCustom-made mandibular advancement devices (MADs) are reported as providing higher efficacy rates compared with thermoplastic heat-moulded MADs but at the price of higher costs and treatment delays.ObjectiveTo determine whether a thermoplastic heat-moulded titratable MAD (ONIRIS; ONIRIS SAS, Rueil Malmaison, France) is non-inferior to a custom-made acrylic titratable MAD (TALI; ONIRIS SAS, Rueil Malmaison, France) for obstructive sleep apnoea (OSA).MethodsWe conducted a multicentre, open, randomised c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…A randomized controlled trial demonstrated that a thermoplastic heat-molded titratable MAD was non-inferior in the short-term to a custom-made acrylic MAD. Therefore, such a thermoplastic titratable MAD can be used as a simple, cheap, and ready to use method to identify patients likely to benefit from long-term MAD therapy [22].…”
Section: Types Of Oral Appliancesmentioning
confidence: 99%
“…A randomized controlled trial demonstrated that a thermoplastic heat-molded titratable MAD was non-inferior in the short-term to a custom-made acrylic MAD. Therefore, such a thermoplastic titratable MAD can be used as a simple, cheap, and ready to use method to identify patients likely to benefit from long-term MAD therapy [22].…”
Section: Types Of Oral Appliancesmentioning
confidence: 99%
“…50,51,53 Twenty-one studies were included in the meta-analysis that evaluated minimum oxygen saturation. Twenty-nine investigations were excluded: 12 22,23,29,30,32,38,44,54,57,66,67,69 did not report the data, 12 24,33,36,40,49,50,59,[62][63][64][65]68 reported ODI instead of minimum oxygen saturation, 3 report together data of study and control groups at baseline, 26,48,56 1 study did not report standard deviations but only P-values without specific reference to baseline data 52 and 1 study reported the mean oxygen saturation instead of minimum oxygen saturation. 51 The MB showed higher effectiveness than DB in improving both the success rate ( Figure 2) and the minimum oxygen saturation (Figure 3).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Six studies compared MB MADs with DB MADs, 21‐26 12 studies compared DB MADs with CPAP, 27‐38 7 studies compared DB MADs with placebo, 39‐45 one study compared DB MAD with CPAP and placebo, 46 one study compared DB MADs with different vertical degrees, 47 one study compared different mandibular advancement degrees of the same DB MAD 48 . Five papers compared different titratable DB MADs, 49‐53 another investigation compared a titratable DB MAD with a non‐titratable DB MAD, 54 one study compared the efficacy of the same DB MAD with and without vertical elastic bands, 55 2 studies compared a DB customised MAD with a non‐customised MAD 56,57 and 3 studies compared DB MADs with other therapies like a tongue retaining device 58 and the positional therapy 59,60 . Three studies compared different mandibular advancement degrees of a MB MAD, 61‐63 2 studies compared a MB MAD with ENT surgery, 64,65 one study compared a customised with a non‐customised MB MAD 62 and 4 studies compared a MB MAD with placebo 66‐70 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Thorax , Pepin and colleagues present a parallel group, non-inferiority trial of two titratable devices: one thermoplastic and one customised acrylic 13. The study recruited CPAP treatment failures or refusers who were non-obese (body mass index <30 kgm 2 ) with moderate–severe OSA (AHI >15).…”
mentioning
confidence: 99%